An analysis method for electricity consumption in peak load period of summer based on regression analysis - Yuze CHEN; Lei LI; Xuemin FANG; Jian LIU; Jiakui ZHAO; Yuxi LIU; Songlin ZUO (Dianxin kexue)
A method for analyzing the relationship between daily maximum temperature and electricity consumption during peak load period was proposed.Firstly,the relationship between maximum temperature and electricity consumption was quantified by Pearson correlation coefficient.Secondly,the functional relationship was established using regression and solved by least squares method.The quantified result of the relationship between maximum temperature and electricity consumption was then acquired.The empirical research shows the proposed method for electricity consumption analysis during peak load period of summer can quantify the variation of daily electricity consumption caused by temperature change and predict electricity consumption of the next few days according to the analysis result.